Desain, Simulasi dan Analisis Peningkatan Range Resolution Sistem Radar FMCW - Mohamad Ansori (President University, 2016)
Range resolution as one of the parameters of the radar system becomes very important and need to be upgraded to provide accurate target distance information. Increased bandwidth can be done however is limited to devices for Direct Digital Synthesizer (DDS) that are used and will enlarge the noise and power consumption of system Frequency Modulated Continuous Wave (FMCW) radar. To improve range resolution, output signal and bandwidth linieritas chirp both plays is very important and the sampling rate of the engineering efforts for improved range resolution still experience barriers when based on peak detection. So to improve range resolution alternatives that can do that is maintain linieritas or increase bandwidth and not just based on peak detection. In this paper are discussed improved range resolution without increasing bandwidth using curve fitting method by way of comparing the output signal of the mixer and beat frequency shift signal mixer output to both match (match). Error of measurement range resolution is affected by the phase errors due to the lack of frequency of linieran beat, so that needs to be done shifted frequency curve fitting method using beat against the sweep of raw data (output ADC) to earn optimum beat frequency (optimum resolution range). Range resolution for Radar Demonstration Kit (RDK) using curve fittng methods obtained results an increase of 30% and the shifting of the beat frequency of 3KHz.